Pengaruh Compensation dan Work-Life Balance terhadap Turnover Intention Generasi Z Dimediasi Job Satisfaction - Aripah, Aripah; Ramadania, Ramadania; Yakin, Ikram; Hasanudin, Hasanudin (Innovative: Journal Of Social Science Research, 2025)
This study examines the impact of compensation and work-life balance on Generation Z employees' intention to leave apparel retailers in the Jawai sub-district, using job satisfaction as a mediating element in this relationship. This research employs a quantitative methodology utilizing an explanatory causal research design. Data collection was performed via an online questionnaire and assessed using a five-point Likert scale. The study's population comprised 154 employees from 48 apparel retailers in the Jawai sub-district. This study utilized a sample of 120 employees that fulfilled the research criteria, specifically individuals aged 18 to 27 years. The participants in this study were chosen by a purposive sampling method. The Structural Equation Modeling Partial Least Squares (SEM-PLS) method was employed for data analysis with SmartPLS 4 software. The findings indicated that compensation and work-life balance had a favorable and significant influence on turnover intention. Moreover, job satisfaction has been demonstrated to mediate the association between compensation and turnover intention, as well as between work-life balance and turnover intention. This study's results are anticipated to provide practical insights for Clothing Store management in developing efficient human resource management strategies, as well as theoretical advancements in the field of human resource management concerning Generation Z.